Potential Future Ore Discovery At The Zinc Corporation Limited And New Broken Hill Consolidated Limited Mines At Broken Hill - Milton D. W; Booth S. A (The Australasian Institute of Mining and Metallurgy, 1983)
Stratabound/stratiform and remobilised mineralisation have been recognised as the two dominant styles of mineralisation which constitute the Broken Hill ore deposit. Recognition of prospective sites for accumulation of ore depends on understanding the heterogeneity of the ore environment and the distribution of the two styles of mineralisation. The internal stratigraphy of the Broken Hill ore deposit and its enveloping rocks, is described, and a generalised stratigraphic setting of the stratiform mineralisation is outlined. Fhiphasis is placed on the existence of closely-spaced sub-basins as potential sites for ore accumulation close to the Broken Hill ore deposit. Further from the immediate ore environment, recognition of the same diagnostic stratigraphic sequence